Students’ Reactions to Peer Violence in Relation to Their Perception of Risk and Protective Factors in the School Environment - Katarina Serdar Čerpnjak; Matea Belošević; Martina Ferić (Društvene i Humanističke Studije)
Global data shows that peer violence and bullying are widespread problems and that the consequences of these behaviours are significant for the future development of children and youth. This study aims to determine: (1) whether there are differences in the witnessing of peer violence depending on the educational level and gender of the students, (2) whether there are differences in students’ reactions to peer violence depending on educational level, gender, and perceptions of risk and protective factors in the school environment. The sample consisted of 2,188 students (aged 10 to 19 years; 48,1% female) in the towns of Jastrebarsko and Samobor. The modified version of the CTC Youth Survey was used. The following statistical methods and analyses were used: descriptive statistics, Mann-Whitney U test, Chi-square test and Cramer’s V. The results showed that a higher percentage of elementary school students reported witnessing peer violence than high school students. In terms of response to peer violence, elementary school students were more likely than high school students to ignore peer violence as if it was none of their business, to be amused, but also to try to do something to prevent peer violence. Regarding gender differences in students’ responses to peer violence, it was found among elementary and high school students that boys tended to ignore peer violence as if it was none of their business and that they often “join in the party”. Concerning protective factors in the school environment,it was found that elementary and high school students who perceive more opportunities and recognition for prosocial involvement at school are more likely to try to take action against peer violence. On the other hand, elementary school students who had not experienced academic failure were found to be more likely to react actively to stop peer violence, while high school students did not differ in their reaction to peer violence, regardless of whether or not they had experienced academic failure. The results of this study could provide a basis for planning evidence-based prevention interventions to promote positive development and/or prevent peer violence in children and youth.